Balkan Village - Sanders, Irwin T. (Irwin Taylor), 1909-2005 (Book collections on Project MUSE., 2016)
In the Balkans today Communism, with its dynamic drive for power and sense of mission, is charging against the Balkan peasant mass, a patient, religious, tradition-bound people tilling their beloved soil. Dragalevtsy, the Balkan village described by Mr. Sanders, brings this struggle into focus. The book details the way of life of a tranquil rural folk clinging to a Bulgarian mountainside, in the shadow of a twelfth- century monastery--their history, economic system, marriage customs, family life, and reluctant yielding to the ways of the western world. On September 6, 1944, Dragalevtsy peasants awoke to find posters in the streets proclaiming the advent of Communism. The concluding chapters of the book give a vital, personalized insight into the economic and social forces now at work in the Balkans.